2021
DOI: 10.1021/jacs.1c01173
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Crossed [2 + 2] Cycloaddition Promoted by Visible-Light Triplet Photosensitization: Expedient Access to Polysubstituted 2-Oxaspiro[3.3]heptanes

Abstract: This paper describes an intermolecular crossselective [2 + 2] photocycloaddition reaction of exocyclic arylidene oxetanes, azetidines, and cyclobutanes with simple electrondeficient alkenes. The reaction takes place under mild conditions using a commercially available Ir(III) photosensitizer upon blue light irradiation. This transformation provides access to a range of polysubstituted 2-oxaspiro[3.3]heptane, 2-azaspiro[3.3]heptane, and spiro[3.3]heptane motifs, which are of prime interest in medicinal chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Recently, this type of photochemical activation gained increasing attention in organic synthetic photochemistry, because triplet excited substrates can exhibit reactivities that are unattainable from their electronic ground states and their singlet-excited states . Specific examples include the photocatalytic generation of singlet oxygen for pericyclic reactions, cycloadditions, E/Z isomerizations, syntheses of cyclopropanes, sensitization of nickel catalysts, the carbocyclization/ gem -diborylation, and the disulfide–ene reaction . Direct excitation of the substrates to their triplet excited states is spin-forbidden, and intersystem crossing from singlet to triplet excited states is frequently very inefficient in organic compounds; hence, metal-based triplet sensitizers are vital for many of these reactions .…”
mentioning
confidence: 99%
“…Recently, this type of photochemical activation gained increasing attention in organic synthetic photochemistry, because triplet excited substrates can exhibit reactivities that are unattainable from their electronic ground states and their singlet-excited states . Specific examples include the photocatalytic generation of singlet oxygen for pericyclic reactions, cycloadditions, E/Z isomerizations, syntheses of cyclopropanes, sensitization of nickel catalysts, the carbocyclization/ gem -diborylation, and the disulfide–ene reaction . Direct excitation of the substrates to their triplet excited states is spin-forbidden, and intersystem crossing from singlet to triplet excited states is frequently very inefficient in organic compounds; hence, metal-based triplet sensitizers are vital for many of these reactions .…”
mentioning
confidence: 99%
“…The arylidene cyclopentane 6 and cyclohexane 7 were found to be less effective for the reaction and in particular, the former ( 6 ) was almost totally unsuccessful. Although the mechanism remains unclear, Knowles and Romanov-Michailidis recently reported that a similar trend is observed in photosensitized [2 + 2] cycloadditions [ 48 ]. Since their report was not a [4 + 2] but a [2 + 2] reaction and they proposed an energy transfer mechanism as opposed to an electron transfer pathway, it cannot be directly compared to our results.…”
Section: Resultsmentioning
confidence: 82%
“…However, both landmark studies are contingent on excitation of another chromophore followed by a bimolecular quench with the vinyl boron species; direct EnT to the alkenyl boron is not anticipated. In 2021, Yoon and co‐workers provided strong evidence to support this phenomenon (Scheme 18, top) [102] . In the development of their photocatalysed synthesis of complex borylated architectures a strategic control reaction, removing the conjugated system, resulted in no cyclisation.…”
Section: Photochemical Strategies Retaining the C−b Bondmentioning
confidence: 97%